Ameliorative effect of low molecular weight peptides from the head of red shrimp (Solenocera crassicornis) against cyclophosphamide-induced hepatotoxicity in mice. (September 2020) - Jiang, Shuoqi; Zhang, Zhuangwei; Yu, Fangmiao; Zhang, Zhoufeng; Yang, Zuisu; Tang, Yunping; Ding, Guofang
Graphical abstract: Highlights: Low molecular-weight peptides were prepared from Solenocera crassicornis head. SCHPs-F1 ameliorated hepatotoxicity induced by cyclophosphamide in mice. SCHPs-F1 restored endogenous antioxidants levels by activating the Nrf2 signal. SCHPs-F1 suppressed hepatic inflammation through NF-κB signal pathway. SCPHs-F1 relieved CTX hepatotoxicity as functional component. Abstract: Our study was aimed at investigating the protective effect of low molecular weight peptides (SCHPs-F1) from red shrimp ( Solenocera crassicornis) head against cyclophosphamide-induced hepatotoxicity in mice. We found that SCHPs-F1 treatment dose-dependently normalized the biochemical markers, hepatic index, and total CYP450 enzyme content in CTX-induced hepatotoxicity in mice. SCHPs-F1 also ameliorated the CTX-mediated structural disorders of the hepatic tissue. Western blot results suggested that SCHPs-F1 significantly restored the levels of endogenous antioxidants (CAT, T-AOC, GSH-Px, SOD and MDA levels) through activating the Nrf2 signal by upregulating the expression of GCLM, HO-1, and NQO-1. Moreover, SCHPs-F1 improved the CTX-induced hepatotoxicity by inhibiting of NF-κB signal responses and down-regulating the expression of the inflammatory factors (IL-1β, IL-6, IFN-γ and TNF-α). These findings suggest that SCHPs-F1 can regulate Nrf2 and NF-κB signaling pathways and reduce the oxidative stress and inflammation in CTX-induced hepatotoxicity. Overall, SCHPs-F1 are value-added food ingredients for alleviating CTX-induced hepatotoxicity.